Effect of Black Tea Powder on Antioxidant Activity and Gel Characteristics of Silver Carp Fish Balls - Jinling Hong; Jiaying Wu; Yanhong Chen; Zedong Jiang; Yanbing Zhu; Zhipeng Li; Xianmu Chen; Hui Ni; Mingjing Zheng (Gels, 2023)
The effect of black tea powder on the antioxidant activity and gel characteristics of fish balls from silver carp were investigated after freezing storage for 7 days. The results show that black tea powder with different concentrations of 0.1%, 0.2% and 0.3% (w/w) could significantly increase the antioxidant activity of fish balls (p < 0.05). In particular, at the concentration of 0.3%, the antioxidant activity was the strongest among these samples, where the reducing power, DPPH, ABTS and OH free radical scavenging rate were up to 0.33, 57.93%, 89.24% and 50.64%, respectively. In addition, black tea powder at the level of 0.3% significantly increased the gel strength, hardness and chewiness while greatly reducing the whiteness of the fish balls (p < 0.05). ESEM observation found that the addition of black tea powder could promote the crosslinking of proteins and reduced the pore size of the gel network structure of the fish balls. The results suggest that black tea powder could be used as a natural antioxidant and gel texture enhancer in fish balls, which we found to be much related to the phenolic compounds of black tea powder.